Do Sanctions Affect Growth? - Ohyun Kwon; Constantinos Syropoulos; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2022)
Direct measures of the economic impact of sanctions are contaminated by the endogeneity that arises when other events in target countries (e.g., civil or interstate conflicts, political independence, etc.) instigate the imposition of sanctions. To address this issue, we propose a novel instrument, sender's aggressiveness, captured by the number of sanctions imposed in a given year. After establishing the validity of this instrument, we quantify the impact of sanctions on growth in sanctioned states and show that, on average, an additional sanction decreases contemporaneous real GDP per capita in target states by 0.39 percent. We also substantiate the presence of a significant (in magnitude) downward bias in the corresponding OLS estimates and demonstrate that the effects of sanctions on growth vary widely depending on the types of sanctions considered, their purported objectives, measures of their success, and the duration of their effects.
Keywords: F43; F51; F63; 330; real GDP per capita growth; trade sanctions; smart sanctions; long-run effects